Analisis Konstruksi Hukum Perpanjangan Masa Jabatan Kepala Desa Menjadi Sembilan Tahun dan Implikasinya Terhadap Demokrasi - Hujriman man (DOKTRINA: JOURNAL OF LAW, 2023)
Indonesia is a legal state that adheres to the current democratic system. A legal state upholds the constitution and limits on powers. The tenure of the Village Head is regulated by Law Number 6 of 2014 concerning Villages which regulates the tenure of the Village Head for 6 years for 3 periods. However, over time the DPR initiated to change the tenure of the Village Head to 9 years for 2 periods. This is a descriptive study focusing on the legal construction of extending the tenure of office of the Village Head to 9 (nine) years in the perspective of constitutionalism and a democratic system. This research used normative juridical method with statutory, historical, and conceptual approaches. The results show that extending the tenure of the village head to 9 years is contrary to the spirit of the legal state and constitutionalism and it indicates the setback to democracy.